Identification of DIM-7, a protein required to target the DIM-5 H3 methyltransferase to chromatin - Lewis, Zachary A. (National Academy of Sciences, 2010)
Functionally distinct chromatin domains are delineated by distinct posttranslational modifications of histones, and in some organisms by differences in DNA methylation. Proper establishment and maintenance of chromatin domains is critical but not well understood. We previously demonstrated that heterochromatin in the filamentous fungus Neurospora crassa is marked by cytosine methylation directed by trimethylated Lysine 9 on histone H3 (H3K9me3). H3K9me3 is the product of the DIM-5 Lysine methyltransferase and is recognized by a protein complex containing heterochromatin protein-1 and the DIM-2 DNA methyltransferase. To identify additional components that control the establishment and function of DNA methylation and heterochromatin, we built a strain harboring two selectable reporter genes that are silenced by DNA methylation and employed this strain to select for mutants that are defective in DNA methylation (dim). We report a previously unidentified gene (dim-7) that is essential for H3K9me3 and DNA methylation. DIM-7 homologs are found only in fungi and are highly divergent. We found that DIM-7 interacts with DIM-5 in vivo and demonstrated that a conserved domain near the N terminus of DIM-7 is required for its stability. In addition, we found that DIM-7 is essential for recruitment of DIM-5 to form heterochromatin.